2022
DOI: 10.1101/2022.08.26.22279246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and Clinical Validation of a Miniaturized Finger Probe for Bedside Hemodynamic Monitoring

Abstract: Background: Hypertension, or elevated blood pressure (BP), is a marker for many cardiovascular diseases and can lead to life-threatening conditions such as heart failure, coronary artery disease, and stroke. BP monitoring using a traditional arm cuff device is often inconvenient and possibly painful in long-term use, i.e. during sleep. Methods: We present a miniature cuffless tonometric finger probe system, that uses the oscillometric method to measure blood pressure (BP). Our approach uses a motorized press t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…However, the accuracy of the continuous BP measurement in any VUT method depends heavily on the accuracy of the oscillometric calibrations performed at certain intervals. This is usually done with a brachial cuff, but in our previous study we have shown that it can be done robustly with the finger tonometry method [27], [35].…”
Section: ) Challengesmentioning
confidence: 99%
“…However, the accuracy of the continuous BP measurement in any VUT method depends heavily on the accuracy of the oscillometric calibrations performed at certain intervals. This is usually done with a brachial cuff, but in our previous study we have shown that it can be done robustly with the finger tonometry method [27], [35].…”
Section: ) Challengesmentioning
confidence: 99%
“…The developed instrument consists of a pressure sensor, optionally a PPG unit, and a motor that applies external compression force to the fingertip, as shown in Figure 1b. [13,17] To measure BP, the user places their fingertip on top of the sensor, and the compression force is then gradually increased. The recorded pressure and PPG signal is processed to extract the oscillometric envelope, from which the BP values can be estimated.…”
Section: Introductionmentioning
confidence: 99%
“…An oscillometric response can be recorded with a pressure cuff, with an optical photoplethysmography (PPG) sensor [14] or via a finger pressing method. [13,[15][16][17] In this study, we present results from compact instrument for measuring hemodynamics at the bedside designed to have similar form factor as in commonly used pulse oximeters (Figure 1a). The developed technology is presented and analyzed in three different embodiments, all sharing the same fundamental technology.…”
Section: Introductionmentioning
confidence: 99%